Densification of lightweight aluminum borate ceramics by direct sintering of milled powders - Hernández, María Florencia (2018)
Dense aluminum borate (Al18B4O33) materials were processed by simple milling-sintering of aluminum borate powders obtained by reacting calcined alumina and fine boric acid at temperatures of around 600–800ºC. The effect of milling on the grain size and sintering behavior of the aluminum borate powders was also determined. Sintering began at around 1000°C and was limited by the thermal decomposition (T > 1300 °C) of the borate in to alumina and boron oxide, which volatilize at this temperature. Sub-angular and medium spherical sintered grain microstructures were developed. A hardness of 6 GPa and bulk density below 2.5 g/cm3 were achieved. The results are accomplished encouraging the structural applications of borate materials.